RESILIENSI EKONOMI KELUARGA DALAM PERGESERAN PERAN GENDER: STUDI TENTANG PEREMPUAN SEBAGAI BREADWINNER DI DESA GINTUNGAN - M. Nurul Fahmi; Fathudin Fathudin; Siti Chasanah; Mustahal Mustahal; Miftahur Rahman (LP2M Universitas Ibrahimy, 2026)
Family economic resilience is increasingly influenced by shifts in gender roles, particularly when women assume the position of primary breadwinner in the household. This study aims to analyze the dynamics of gender role transformation and its contribution to family economic resilience in Gintungan Village. The research was motivated by socio-economic changes that have encouraged women to participate more actively in income-generating activities, challenging traditional gender norms within the family structure. This study employed a qualitative descriptive approach using a case study design. Data were collected through in-depth interviews, participant observation, and documentation involving women breadwinners and their family members in Gintungan Village. The data were analyzed using data reduction, data display, and conclusion drawing techniques. The results show that women as primary breadwinners play a significant role in maintaining household economic stability through income diversification, financial management, and adaptive survival strategies. The shift in gender roles has also influenced household decision-making patterns and family power relations. However, this transformation creates both opportunities for empowerment and challenges related to double burdens and social perceptions. The study concludes that the transformation of gender roles strengthens family economic resilience when supported by adaptive family cooperation, effective communication, and shared responsibilities between family members.